Themes and Flux in British Politics Evolution, Change and Turbulence - Duncan McTavish (2019)
Themes and Flux in British Politics provides readers with an engaging and informative overview of the development, change and turbulence in British politics today. It explores the extent to which the ‘old approaches’ to politics and policy are becoming less relevant in the contemporary and emerging UK environment and makes sense of the most significant aspects of the moment: political and electoral alignment, referenda, Brexit and the EU, relationship between UK and devolved governments, and key impact-related developments internationally. As such, it is an essential read for students and observers of British political life who need pointed, expert coverage to help make sense of these exceptional political times.